Poem "LXI", prison motive, human transcendence and morality or ethics of the good - Castillo Sánchez, Wellington (2020)
According to Espejo Asturrizaga, when César Vallejo was imprisoned, between November 1920 and February 1921, he wrote eight poems that were included in Trilce; one of them, the one marked with the Roman numeral LXI, whose initial verse is "Esta noche desciendo del caballo", does not reveal, like others, the vision of prison or physical imprisonment, but a form of human transcendence that establishes a moral or ethical rule of good in the chaotic and agonizing human existence. We develop this hypothesis from a historical and socio-cultural perspective, supported by the analysis, interpretation and literary assessment from which we consider that the poem "LXI" is interrelated with the thematic and formal elements of the collection, in a current and futuristic vision, which allows us to notice that in Vallejo's poetry not everything is said, nothing is definitive; on the contrary, everything is a permanent finding and this confirms its validity.